Predictive value of the Kuijer score for bleeding and other adverse in-hospital events in patients with venous thromboembolism. (15th April 2021) - Keller, Karsten; Münzel, Thomas; Hobohm, Lukas; Ostad, Mir A.
Abstract: Background: Venous thromboembolism (VTE) constitute a major global burden of disease. Current international guidelines recommend treatment with anticoagulant therapy after VTE for a duration of at least 3 months. Since anticoagulation also imposes an increased risk for bleeding events, the individual risk has to be evaluated to determine adequate treatment plans. Methods: The nationwide German inpatient sample of the years 2005–2017 was used for this analysis. Hospitalized VTE patients were stratified according to Kuijer risk class and the performance of the Kuijer score was evaluated to predict adverse in-hospital events. Results: Overall, 1, 204, 895 VTE patients were treated between 2005 and 2017 in Germany and were included in the present study (839, 143 patients had deep venous thrombosis and/or thrombophlebitis and 669, 881 patients pulmonary embolism). According to Kuijer risk class stratification, in total, 176, 723 (14.7%) of the hospitalized VTE patients were classified as low risk, 914, 964 (75.9%) as intermediate risk and 113, 208 (9.4%) as high risk. A higher Kuijer risk class was predictive for in-hospital death (odds ratio [OR] 1.99 [95% confidence interval (CI) 1.96–2.02], P  < 0.001), major adverse cardiovascular and cerebrovascular events (MACCE, OR 1.90 [95%CI 1.87–1.93], P  < 0.001), intracerebral bleeding (OR 1.28 [95%CI 1.14–1.44], P  < 0.001), gastrointestinal bleeding (OR 1.56 [95%CI 1.48–1.64], P  < 0.001) as well as necessity of transfusion of blood constituents (OR 2.94 [95%CI 2.88–3.00], P  < 0.001) independently of important comorbidities. Conclusions: The Kuijer score is an important risk stratification tool to predict individual risk regarding in-hospital outcomes comprising major bleeding events such as intracerebral bleeding and necessity of transfusion of blood constituents, but also in-hospital mortality and MACCE in VTE patients. Highlights: Kuijer score is an important risk stratification tool to predict different outcomes in VTE patients. Kuijer score revealed a good predictive performance for major bleeding events in VTE. In addition, Kuijer score was also predictive for in-hospital mortality and MACCE in VTE.